2022
DOI: 10.31729/jnma.7608
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among Patients with Chronic Kidney Disease Undergoing Haemodialysis in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Chronic kidney disease is a global public health problem with psychological issues and other adverse issues like renal failure, cardiovascular disease, and premature deaths. This study aimed to find out the prevalence of anxiety and depression among patients with chronic kidney disease undergoing haemodialysis in a tertiary care centre. Methods: A descriptive cross-sectional study was done among patients with chronic kidney disease undergoing haemodialysis in the Department of Medicine, Nephrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The hemodialysis process negatively affects the social, financial, and psychological well-being of all patients (Ginieri-Coccossis et al, 2008). Furthermore, patients with end-stage renal failure go through major changes and adjustments in terms of their personal, professional, and social lives (Kimmel, 2001;Sharma et al, 2022). According to Kimmel (2001) and Goyal et al (2018), hemodialysis patients must adjust their lifestyle and personal changes in sexual interest and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodialysis process negatively affects the social, financial, and psychological well-being of all patients (Ginieri-Coccossis et al, 2008). Furthermore, patients with end-stage renal failure go through major changes and adjustments in terms of their personal, professional, and social lives (Kimmel, 2001;Sharma et al, 2022). According to Kimmel (2001) and Goyal et al (2018), hemodialysis patients must adjust their lifestyle and personal changes in sexual interest and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging empirical evidence suggests a robust correlation between nursing quality, treatment effectiveness, and patient treatment compliance. Hence, improvement of the quality of care and daily living guidance for hemodialysis can enhance the treatment compliance of patients and improve their prognosis, thereby effectively improving treatment outcomes [7,8] . Nonetheless, routine nursing is too single-facet to provide integrated nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…The results of several relevant studies have shown that the prevalence of symptoms ranges from 40.7% to 92.3% in HD patients [ 6 9 ]. Among the physical symptoms, skin itching, fatigue, sleep disorder, and other symptoms are the most prominent [ 10 13 ], while among the psychological symptoms, anxiety and depression are particularly common [ 10 , 14 , 15 ]. Especially in older patients, with increasing age, the symptoms occur more often and are more severe, thereby negatively affecting the patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%